2002
DOI: 10.1007/bf03324464
|View full text |Cite
|
Sign up to set email alerts
|

Factors of importance to the caregiver burden experienced by family caregivers of Parkinson’s disease patients

Abstract: To ease the caregiver burden, attention should be paid to patient functional status and caregivers depressive symptoms. The sense of coherence in caregivers is probably more difficult to influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 20 publications
10
91
3
Order By: Relevance
“…Significant stressors identified in this study, specifically the patient's severity of illness, length of disease, and hours of caregiving, were similarly reported in other PD research studies as major stressors for caregivers [14,15,24] . The caregiver study results indicated that the quality of the caregiver-veteran relationship was significantly related to stress levels; this finding was also supported by other researchers [19,20] .…”
Section: Discussionsupporting
confidence: 76%
“…Significant stressors identified in this study, specifically the patient's severity of illness, length of disease, and hours of caregiving, were similarly reported in other PD research studies as major stressors for caregivers [14,15,24] . The caregiver study results indicated that the quality of the caregiver-veteran relationship was significantly related to stress levels; this finding was also supported by other researchers [19,20] .…”
Section: Discussionsupporting
confidence: 76%
“…Because of the significant finding of increased caregiver burden in friends and family members of individuals with Alzheimer's disease [11][12][13], a similar increased burden would be likely in caring for individuals with PD. Supporting this concept, two recent studies demonstrated that caregiver burden in PD is associated with patient functional status, depressive symptoms, time since onset of PD, and other health-related issues [14][15]. Consequently, a sharper focus on the burden experienced by PD caregivers appears warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Providing care to a family member with PD can have far-reaching effects on the caregiver's social activities, emotional health, and stress (Caap-Ahlgren & Dehlin, 2002;Edwards & Scheetz, 2002). Even though medication is initially effective at controlling patients and allowing them to function normally while making little, if any, physical demands, the caregiver may experience emotional stresses related to uncertainty about the prognosis.…”
Section: Introductionmentioning
confidence: 99%